Deskripsi Kemampuan Penalaran Adaftif Siswa di SMP Negeri 5 Purwokerto Ditinjau dari Keaktifan Belajar Siswa - Hasya Putri Afifian; Eka Setyaningsih (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2019)
This study aims to describe the adaptive reasoning skills of students in SMP Negeri 5 Purwokerto in terms of student learning activeness in the subject system of two-variable linear equations. This study uses qualitative research methods and uses the Miles and Huberman model, which includes data reduction, data presentation (display data) and conclusions (verification/conclusion drawing). Sources of data in this study were students of class VIII H. The research subjects were obtained using purposive sampling techniques, and students were categorized into three categories, namely students with high, medium and low learning activeness categories. Each group was selected by three students for research purposes. Data collection methods in this study used questionnaires, tests, interviews and documentation. Based on the results of the study it can be said that students who have high learning activeness are able and meet three of the five indicators of adaptive reasoning skills appropriately, students who have active learning are not yet adequately fulfilling indicators of adaptive reasoning skills appropriately, and students who have low learning activeness have not been able to and mastering precisely the indicators of adaptive reasoning abilities.